Pengaruh Customer Experience di Outlet dan Pelayanan Melalui Aplikasi Online terhadap Loyalitas Konsumen pada Mie Gacoan Cabang Jakabaring Palembang - Mukmin Hidayat; Sabeli Aliya (CV. ITTC INDONESIA, 2025)
The rapid growth of the culinary industry in metropolitan areas such as Palembang has intensified competition among businesses striving to attract and retain customers. One strategic aspect in building consumer loyalty is customer experience at the outlet, along with the ease and quality of service provided through online ordering applications. The phenomenon observed at Mie Gacoan Jakabaring Palembang indicates that customers are not only drawn to the variety of menu options and affordable prices, but also to the overall dining experience and the convenience of digital services. This study aims to analyze the influence of in-store customer experience and online service delivery on consumer loyalty at Mie Gacoan Jakabaring Palembang. A quantitative approach with an associative-causal design was employed. A total of 110 respondents were selected using a simple random sampling technique. Data were collected through a Likert-scale questionnaire. The analysis involved validity and reliability testing, classical assumption tests, multiple linear regression analysis, t-tests, F-test, and the coefficient of determination. The results show that customer experience has a positive and significant effect on consumer loyalty, with a t-value of 4.184 (p = 0.004), while online service delivery also has a positive and significant effect, with a t-value of 5.932 (p = 0.000). Simultaneously, both variables exert a positive and significant influence on consumer loyalty, with an F-value of 18.829 (p = 0.000). These findings highlight the importance of strengthening customer experience and optimizing online services to enhance consumer loyalty.